Mango Supply Chain and Value Chain Analysis from Farm to Market - Mahbub Alam (International Journal of Supply Chain Management, 2018)
Abstract - The study evaluates the traditional mango fruit supply chain and finds opportunities and challenges of traditional practices, and analyses the value chain mango from farm to market. The study also estimates the Benefit Cost Ratio (BCR) for mango farmers and examines the distribution of the added value among the value chain actors-farmers, traders and retailers. A value chain model was developed and confirmed by more than two hundred respondents comprises of all the value chain actors, including farmers, traders, retailers, consumers, and other stakeholders. Both primary and secondary data were used in this research, and a simple statistical techniques were used for analysing the data. The study reveals that there was a huge potential for farmers in growing mango fruit, while the post-harvest loss was found very high and a lots of middlemen were exist in the chain. The result of the value chain analysis shows, farmers share of the added value was the lowest, while the retailers were bagging the highest. The research outcomes need to be applied by the policy makers, researchers and the implementers for the betterment of the farmers and consumers.